Anak Mikhrul: Exposing Gender Inequality in Lampung Custom Practices - Napsiah, Napsiah; Munthe, Hadriana Marhaeni; Ledyawati, Ledyawati; Wahjudin, Lisdawati (UIN Sunan Kudus, 2023)
Traditional practices are one of the factors that cause gender inequality because they consider women to be inferior to the superiority of men. The purpose of this study is to reveal the customary practices of Lampung which then cause gender inequality to be hereditary by focusing on the term mikhrul. By using qualitative research data was collected through interviews with traditional leaders, religious and community leaders. In addition, indirect observation was used to strengthen data that was not disclosed at the time of the interview. Secondary data obtained from journals and books. By using descriptive analysis, the findings of this study are: mikhrul is a customary term that is socialized to girls from a young age which means that girls are daughter-in-law while boys are biological children. Consequence, girls do not have access, participation, and control in the family, because the role of girls is temporary, namely before marriage. Therefore, daughters are only custodians of family assets. Meanwhile, sons have a substitute role for their parents, are responsible for family members who are not yet independent, and have responsibilities for their wives, so that sons have power over all parental assets. In the name of custom, the superiority of sons in the family is passed down from generation to generation, so that women experience gender inequality. responsible for family members who are not yet independent, and have responsibility for the wife, so that the son has power over all the assets of the parents. In the name of custom, the superiority of sons in the family is passed down from generation to generation, so that women experience gender inequality. Responsible for family members who are not yet independent, and have responsibility for the wife, so that the son has power over all the assets of the parents. In the name of custom, the superiority of sons in the family is passed down from generation to generation, so that women experience gender inequality.